Unraveling the Influence of Financial Distress and Fixed Asset Intensity on Tax Avoidance : Review of evidence in the literature - Suci Ramadhani; Sri Rahayu; Wirmie Eka Putra (Greenation International Journal of Economics and Accounting, 2025)
This study investigates the impact of new technology adoption on production costs and the supply curve in the manufacturing industry. Using a quantitative approach, panel data from 50 manufacturing companies were collected over a 5-year period (2020-2024). The main variables analyzed were technological investment (proxy: expenditure on R&D and automation machinery), production cost per unit, and supply volume. The findings indicate that investment in new technology significantly lowers production costs per unit (p<0.05). This reduction enables firms to increase the supply volume at any given price level, which is the fundamental mechanism behind the observed rightward shift of the supply curve. This study provides empirical evidence that technological innovation is a key driver of economic efficiency and production capacity growth, ultimately enhancing a firm's market competitiveness.